NEGOTIATING INNOVATION: A CASE STUDY OF PROJECT-BASED LEARNING FOR ENGLISH SPEAKING IN THE MERDEKA CURRICULUM - Rahma Sakina; Aip Syaepul Uyun; Revi Nur Ridwan; Sri Yunita; Finka Mareta; Nendah Sari Indriani (English Review: Journal of English Education, 2026)
This qualitative case study investigates how an English teacher implemented PjBL in speaking instruction under the Merdeka Curriculum at SMAN Jatinangor, the challenges encountered, and the strategies used to address them. The participants were one English teacher and eleventh-grade social science students. Data were collected through classroom observations, semi-structured interviews, and document analysis. An adapted observation form from Roheni (2022) guided the observations, while interview data were analysed thematically and documents were examined using the READ approach. Data credibility was ensured through triangulation and member checking. The findings reveal a locally adapted nine-stage PjBL model consisting of lesson explanation, group formation, project planning, scheduling, group discussion, progress monitoring, project presentation, assessment, and evaluation. Five main challenges emerged—limited pedagogical mastery, time constraints, student discipline, assessment complexity, and group management—which were further conceptualised into three interrelated constraints: knowledge–skill, temporal–structural, and social–behavioral.